ANTIBACTERIAL ACTIVITY TEST OF CALCIUM HYDROXIDE AND MAULI BANANA (Musa acuminata) STEM EXTRACT GEL MIXTURE AGAINST Enterococcus faecalis - Sukma Ayu Wardani; Dewi Puspitasari; Isyana Erlita (Dentino : Jurnal Kedokteran Gigi, 2023)
Background: The use of calcium hydroxide as an intracanal medicament has several weaknesses that can cause side effects, including chronic inflammation in the periapical tissue and resistance to several bacteria, one of which is Enterococcus faecalis. The bacteria are the most resistant microorganism to calcium hydroxide due to a high pH tolerance capability. This weakness is the reason for finding alternative materials that can combine with calcium hydroxide. Mauli banana stem has bioactive compounds such as tannins, saponins, alkaloids, and flavonoids which have antibacterial and anti-inflammatory effects. Therefore, combined with calcium hydroxide may exhibit good characteristics as an intracanal medicament. Purpose: To analyze the antibacterial activity of the calcium hydroxide and mauli banana (Musa acuminata) stem extract gel mixture against Enterococcus faecalis. Methods: The research is a pure experimental study with a post-test only with control group design that uses 4 treatment groups, including calcium hydroxide and mauli banana stem extract gel mixture at a concentration of 25%; 37,5%; 50%; and control with each of 9 replications. The parameter measured was the diameter of the inhibition zone that formed on Mueller Hinton Agar. Result: One Way Anova and Bonferroni Post Hoc tests showed significant differences between each treatment group. Conclusion: The mixture of calcium hydroxide and mauli banana stem extract gel had antibacterial activity against Enterococcus faecalis. The mixture of calcium hydroxide and mauli banana stem extract gel at 50% concentration obtained the highest inhibition zone. Keywords: Antibacterial activity, Calcium hydroxide, Enterococcus faecalis, Musa acuminata